CONCEPT OF INTEGRATIVE ISLAMIC EDUCATION - Sutiono Sutiono; Iman Abdul Ridho (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
The background of this research is the dichotomy of Islamic education. This dichotomy is the cause of the backwardness of Islamic education, so that the assumption arises that only religious knowledge must be learned. General knowledge is considered secular and not required to be learned, so that Pesantren and Madrasah are considered to represent religious education institutions, while schools are a place for general education. To revive a civilization that has experienced centuries of dullness, Muslims must advance science, technology and education integratively. This research aims to find out the concept of integrative Islamic education, as well as to answer the question of how the concept of integrative Islamic education and how the relevance of integrative Islamic education to the progress of the people and nation. This research method is library research. library research is research whose data collection techniques are carried out by library research, based on readers of literature that has information and has relevance to the research topic. Thus, library research is a series of activities related to library data collection methods, reading and recording and managing research materials. In the findings of the results of this study, integrative education is an educational paradigm that asks Muslims who study not only the sciences derived from the Quran and hadith, but also the general sciences or what is called science. Even Muslims can learn anything, integrative education thinking. The concept of integrative education is a must because it determines Muslims. Muslims are underdeveloped because of the current dichotomy of science. Therefore, the integration of Islamic education is currently very relevant. The program developed is an effort to apply science and technology to overcome the backwardness, poverty, and dependence of Muslims.